Using team efficacy surveys to help promote self-and-team-efficacy among college athletes - DeRohan, N.; Nagy, C.; Meisenhelder, H.; Katayama, A. D. (The Sport Journal, 2011)
Abstract The purpose of this study was to track and understand attitudinal changes and trends among 3 NCAA Division I intercollegiate teams at the United States Air Force Academy (USAFA). We wanted to see if surveys of team efficacy would help promote self-and-team efficacy with respect to team goals and outcomes. Measures of team efficacy and locus of control were measured throughout the season: preseason, mid-season and postseason. Even though the results varied slightly for each sport, common trends were found with respect to team efficacy and their perceived chances for success and team history. Team goals did not fluctuate much throughout the season. However, results from the survey showed a significant drop in team efficacy for both the baseball and women`s basketball teams from preseason to midseason for both internal locus of control: baseball, t(15) = 3.53, p = .003); women`s basketball, t(15) = 3.67, p = .002. A significant drop in the teams external locus of control was also observed for both baseball, t(15) = 4.43, p < .001 and women`s basketball, t(15) = 2.95, p = .010. However, for the hockey team, there was not a significant drop in internal locus of control, t(15) = 1.23, p = .237 or in external locus of control, t(15) = 1.10, p= .289. As the baseball and women`s basketball teams lost more games both their internal and external locus of control dropped. Accordingly, because the Hockey team did not lose as many games from midseason on their locus of control measures did not experience any drop-off.